2021
DOI: 10.3390/ani11113060
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Levels of Inclusion of Apulo-Calabrese Pig Meat on Microbiological, Physicochemical and Rheological Parameters of Salami during Ripening

Abstract: This study focused on the characterization of salami produced with meat from different pig breeds. The aim consisted in evaluating the added value of the inclusion of Apulo-Calabrese meat in the production of salami, which was characterized by production until the end of maturation (1, 30, 60, and 120 days). The experimental design involved three types of salami, two of which were produced by partial inclusion of 50 and 75% of the Italian breed pork meat (S50 and S75, respectively). Physicochemical (pH, aw, fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Nonetheless, a number of studies have shown that a much better response to consumers' demands, in terms of animal-friendly and environmentally sustainable pig production, can be provided by local pig breeds reared in their specific traditional production systems than commercial crossbreds from intensive production systems [6,7]. Studies involving modern and native pig breeds have demonstrated the enhanced meat and fat quality of the latter when reared in outdoor rearing systems [8], especially regarding the intramuscular fat (IMF) content and fatty acid composition [9]. Generally, it is believed that meat is tastier when IMF is higher than 1.5% [10], but for the production of pork destined for high-quality cured products, optimal fat levels are 3.5-4.0% [11].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, a number of studies have shown that a much better response to consumers' demands, in terms of animal-friendly and environmentally sustainable pig production, can be provided by local pig breeds reared in their specific traditional production systems than commercial crossbreds from intensive production systems [6,7]. Studies involving modern and native pig breeds have demonstrated the enhanced meat and fat quality of the latter when reared in outdoor rearing systems [8], especially regarding the intramuscular fat (IMF) content and fatty acid composition [9]. Generally, it is believed that meat is tastier when IMF is higher than 1.5% [10], but for the production of pork destined for high-quality cured products, optimal fat levels are 3.5-4.0% [11].…”
Section: Introductionmentioning
confidence: 99%
“…Primary and secondary lipid oxidation were evaluated by thiobarbituric acid test [(TBARs test), mg of malondialdehyde per kg of sample (mg of MDA/Kg)], and peroxide value [(PV) mgO2/Kg fat] measurement, respectively. Measurements were performed according to the methods proposed by Ambrosio et al ( 2021 ) and Di Paolo et al . ( 2023 ), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Texture profile analysis (TPA) and color evaluation (CIEL*a*b*) were performed on 3 cm thick slices of SM and SR salami. According to Ambrosio et al, 2021 [26], the colorimetric evaluation required a Konica Minolta CR300 colorimeter (Minolta, Osaka, Japan). Color measurements were performed on both the external and internal surfaces (three measurements for each surface).…”
Section: Texture and Color Analysismentioning
confidence: 99%
“…Color measurements were performed on both the external and internal surfaces (three measurements for each surface). For texture profile analysis (TPA), the Shimadzu EZ-Test texturometer (Shimaduz Corporation, Kyoto, Japan) was employed, following the procedures described by Ambrosio et al, 2021 [26]. The following parameters were evaluated from the TPA curve: adhesiveness (N × mm), cohesiveness (N), hardness (N), cohesion (N), gumminess (N), chewiness (N), resilience.…”
Section: Texture and Color Analysismentioning
confidence: 99%